STAKEHOLDER COLLABORATION IN EMPOWERING LOCAL POTENTIAL-BASED TOURISM AWARENESS GROUPS IN PANGARENGAN, SAMPANG - Buadah; Sri Kamariyah; Zainal Fatah (International Journal of Multidisciplinary Reseach, 2026)
This research examines the dynamics of stakeholder collaboration in empowering the Tourism Awareness Group (Pokdarwis) based on local potential in Pangarengan, Sampang Regency. The study is motivated by the shift in public administration toward collaborative governance to optimize coastal resources such as salt ponds and mangrove ecosystems. Using a descriptive qualitative approach, data were gathered through interviews with representatives from the tourism department, village governments, Pokdarwis members, academics, and the private sector. The results indicate that collaboration remains in a transitional phase characterized by